Surface Modification of the LiFePO4 Cathode for the Aqueous Rechargeable Lithium Ion Battery - Tron, Artur; Jo, Yong Nam; Oh, Si Hyoung; Park, Yeong Don; Mun, Junyoung (American Chemical Society, 2017)
The LiFePO4 surface is coated with AlF3 via a simple chemical precipitation for aqueous rechargeable lithium ion batteries (ARLBs). During electrochemical cycling, the unfavorable side reactions between LiFePO4 and the aqueous electrolyte (1 M Li2SO4 in water) leave a highly resistant passivation film, which causes a deterioration in the electrochemical performance. The coated LiFePO4 by 1 wt % AlF3 has a high discharge capacity of 132 mAh g(-1) and a highly improved cycle life, which shows 93% capacity retention even after 100 cycles, whereas the pristine LiFePO4 has a specific capacity of 123 mAh g(-1) and a poor capacity retention of 82%. The surface analysis results, which include X-ray photoelectron spectroscopy and transmission electron microscopy results, show that the AlF3 coating material is highly effective for reducing the detrimental surface passivation by relieving the electrochemical side reactions of the fragile aqueous electrolyte. The AlF3 coating material has good compatibility with the LiFePO4 cathode material, which mitigates the surface diffusion obstacles, reduces the charge-transfer resistances and improves the electrochemical performance and surface stability of the LiFePO4 material in aqueous electrolyte solutions.
Keywords: ELECTROCHEMICAL PERFORMANCE; ELECTRODE MATERIALS; LIMN2O4; BEHAVIOR; LICOO2; NANOCOMPOSITE; CARBON